STUDY OF ENVIRONMENTAL IMPACT ON SCHOOL BUILDING CONSTRUCTION (CASE STUDY: SDN HARJAMUKTI 5, DEPOK CITY) - Alimudin, Alimudin (Universitas Ibn Khaldun Bogor, 2020)
Improvement of education building facilities and infrastructure is needed to improve services to the community. In line with the green building planning, Housing and Settlements Department, Depok City plans to build SDN Harjamukti 5 Public with due regard to environmentally friendly development. The activity is predicted to cause environmental impacts, so a study of environmental impact analysis is needed. The purpose of this study is to determine the baseline condition of the study site and analyze the environmental impacts and obtain ways to overcome the results of the analysis in an effort to minimize the impact that will then be used as a reference in order to properly protect the environment. The method used is survey method. This research uses primary data and secondary data. Primary data include water quality data, ambient air quality and noise data, and flora and fauna data while secondary data include climate data and socio-economic data. The results of the study obtained an analysis of environmental impacts that occur and how to minimize impacts with good handling in order to create a construction that is green building concept.